Salida, tránsito, destierro : una aproximación al imaginario transnacional de los jóvenes - Chabier Gimeno-Monterde (Les Cahiers de Framespa)
Since 2007 we have been analyzing the symbolic imagery of young people from North Africa who migrate alone to Aragon and Southwestern France. In the case of Toulouse, the symbolic is riddled with the presence in its territory of the spatially and socially segregated neighborhoods, with the corresponding symbolic imagery of banishment. According to the interviews and analyses of virtual networks, the iconography of vandalism and exclusion which emanates from the « banlieues » acts both as a pull factor and a deterrent factor in the migration projects of many young people, who prefer to avoid France as a step or as a destination. But it also soaks the imagery of those who remain in Aragon, who vandalize their aesthetic and discourses through mimicry.